Ayurvedic Aspect of Amalaki -A Review - Ray, Shreyosi (International Research Journal of Ayurveda & Yoga, 2022)
Mother Nature has gifted us with various resources for the survival of mankind. Amongst them not only lie the foods that we consume but also a mine of medicines that are being explored each and every day. Amalaki, also known as Indian gooseberry, scientifically known as Emblica officinalis (Syn. Phyllanthus emblica) belonging to the family Euphorbiaceae is such a gem of a drug that is a gift to mankind. Amalaki is used widely as a single drug and as an ingredient of numerous formulations for the betterment of lifestyle and also as treatment procedure. It is known to possess antioxidant, anti inflammatory, hepatoprotective, immunomodulatory, etc. properties. Although, numerous studies regarding amalaki are widely available, there still lies scope for evaluation and analysis on this topic.